مركز الفقه المالكي في الاجتهاد القضائي الأسري الجزائري (باب الزواج نموذجا) - نية مبخوتة ريحانة; العيشي حنان (جامعة محمد بوضياف ـ المسيلة, 2025)
This study aims to analyze the extent to which Maliki jurisprudence influences the judicial reasoning in Algerian family law, using marriage-related cases as a practical model. The research focuses on exploring the legal and jurisprudential foundations underlying the Algerian Family Code, beginning with an overview of the Maliki school one of the major schools of Islamic jurisprudence by defining it, examining the factors behind its spread, and tracing its establishment in Algeria, as well as its central role in legal opinions (fatwa) and judicial rulings. The study further explores the concept of judicial ijtihad in the Algerian legal system, its role as a source of law, and highlights its development, importance in matters of personal status, the reasons that necessitate its use, and its impact on family law judgments. The applied section of the study analyzes a sample of Supreme Court decisions related to marriage, in order to assess their alignment with the principles of Maliki jurisprudence, thereby illustrating the dynamic interaction between traditional Islamic legal heritage and contemporary judicial practice in Algerian family law. تهدف دراستنا لعنوان مركز الفقه المالكي في الاجتهاد القضائي الأسري الجزائري باب الزواج نموذجا إلى تحليل مدى حضور الفقه المالكي في أحكام الاجتهاد القضائي الأسري الجزائري ، لاسيما في قضايا الزواج كنموذج تطبيقي ، وقد تم التركيز على دراسة الأسس الفقهية والقضائية التي تقوم عليها منظومة قانون الأسرة الجزائري، بدءا بتسليط الضوء على المذهب المالكي أحد أعمدة المذاهب الاسلامية الفقهية من حيث تعريفه،عواملانتشاره،إلى حين دخوله الجزائر فضلا عن مكانته في الفتوى والقضاء ، كما تناولت الدراسة مفهوم الاجتهاد القضائي في المنظومة القانونية الجزائرية،ودوره كمصدر من مصادر القانون، مع إبراز تطوره وأهميته في مجال الأحوال الشخصية والدوافع التي تقتضي اللجوء إليه وآثاره في الأحكام الأسرية انتقالا إلى الجانب التطبيقي الذي من خلاله تم تحليل عينة من قرارات المحكمة العليا المتعلقة بقضايا الزواج لقياس مدى توافقها مع أحكام المذهب المالكي بهدف إبراز التفاعل بين المرجعية الفقهية المالكية و الاجتهاد القضائي المعاصر في المجال الأسري.